2012
DOI: 10.5539/ijef.v4n6p70
|View full text |Cite
|
Sign up to set email alerts
|

Operational Value-at-Risk in Case of Zero-inflated Frequency

Abstract: In this paper we analyze operational risk in case of zero-inflated frequency data. We show that standard Poisson distribution does not suit correctly excess zero counts data. Alternatively, Zero-inflated Poisson (ZIP) distribution fits better such data. To assess the benefits of the use of ZIP distribution on operational risk management, we develop two separate aggregate distributions. The first one is based on standard Poisson distribution and the second on ZIP distribution. Note that the severity model is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Following Mouatassim et al [62], suppose that N is the number of outcomes and N 0 is the number of zeros in the data. The likelihood becomes:…”
Section: Appendix A2 Negative Binomial Regression Models and Overdispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Mouatassim et al [62], suppose that N is the number of outcomes and N 0 is the number of zeros in the data. The likelihood becomes:…”
Section: Appendix A2 Negative Binomial Regression Models and Overdispersionmentioning
confidence: 99%
“…As stated in Mouatassim et al [62], the numerical algorithm can be used to find the estimated value of λ. Thus, the estimated value of p logit can then be determined by replacing λ in (A15) or (A16).…”
Section: Appendix A2 Negative Binomial Regression Models and Overdispersionmentioning
confidence: 99%
“…However, in the business studies sciences, such as finance and accounting, it is less common to find applications (e.g. Affinito and Piazza, 2009;Mouatassim et al, 2012).…”
Section: Econometrical Analysismentioning
confidence: 99%
“…The numerical algorithm can be used to find the estimated value of λ. Thus, the estimated value of p logit can be determined by replacing λ in ( 6) or ( 7) (Mouatassim et al, 2012).…”
Section: Zero-inflated Count Data Modelsmentioning
confidence: 99%
“…compare poisson model to the zero inflated model and applied to health insurance data set. Mouatassim, Ezzahid and Belasri(2012) analized operational risk to the zero inflated data and assess the impact of ZIP distribution on the operational capital charge. They concluded that the zero inflated Poisson distribution is better fit then Poisson distribution for modeling operational risk frequency.…”
Section: Literature Reviewmentioning
confidence: 99%